Three-dimensional graphene nanosheet films towards high performance solid lubricants - Chen, F. X. (2021)
Graphene nanosheet films (GNSF) show great potential as solid lubricants. They, however, usually suffer from short lifetime and low load capability, limiting their further engineering application. In this work, we try to address these crucial challenges, for the first time, by inducing a unique three-dimensional microstructure into the GNSF. The as-prepared three-dimensional graphene nanosheet films (3D-GNSF) are composed of many crumpled and partially standing graphene nanosheets (GNS) that overlap with each other and form a three-dimensional interconnected network. The morphology, composition and structure of the 3D-GNSF are investigated in detail using scanning electron microscope, X-ray diffractometer, transmission electron microscope and X-ray photoelectron spectroscopy to deduce their possible formation mechanism. Tribological tests are conducted in air as a function of contact pressure that is up to about 1GPa. The results suggest it is the unique architecture of the 3D-GNSF that quickly produces a compact and stable sliding interface consisting of GNS against GNS, enabling 3D-GNSF as promising solid lubricants with low friction, excellent anti-wear ability, good durability and high load capability.